Conception of context in research of cognitive processes - Martišius, Vaclovas (Psichologija, 2006)
The purpose of the research is to critically assess both the concept of context and interpretation of contexttypes that are used in the field of research of cognitive processes. Many different authors describe the concept of context differently. Some authors, particularly representatives of AI research trend, interpret the notion of context as means of both structurization of knowledge and using it in the process of problem solving, or the whole complex of important conditions and influences of the situation, which make one think of the situation as unique and understandable, while others interpret context as unconscious representations that make an influence on the experiences of individual. Psychologists note frequently that context should not be related with something that is in the centre of attention, i.e. stimulus, or target. Differences of interpretation of context, existing in the works of both AI specialists and psychologists, are, apparently, due to the fact that AI experts investigate intelligence in a rather general manner taking into account its every possible manifestation, while psychologists limit themselves to only making researches in both people’s and animals’ intellectual activities. As the case may be, there’s no reason to attribute the impact of context to only unconscious processes and automatism. It has been established that conscious context sometimes acts upon a target quite differently, compared with unconscious context.
Keywords: agent context; task context; situation context; representations